ABC News – Nightline
News anchor Catherine Crier and reporter Tom Foreman explore the impact of Holocaust on the American society by taking a look at the Jewish Holocaust during WWII and the events in Bosnia- Herzegovina in the early 90s on the occasion of the release of the motion picture "Schindler's List." The report is followed by a live discussion with Letty Cottin Pogrebin (author, lecturer), William Styron (author), and Leon Wieseltier ("New Republic" Literary Editor) moderated by Catherine Crier.